PENERAPAN SISTEM PENCATATAN KEUANGAN ASET BIOLOGIS BERDASARKAN SAK-EMKM PADA USAHA AYAM PETELUR (Studi Kasus Pada Ayodhya Farm Di Desa Sukawana, Kecamatan Kintamani, Kabupaten Bangli, Bali): (Studi Kasus pada Ayodhya Farm di Desa Sukawana, Kecamatan Kintamani, Kabupaten Bangli, Bali) - I Komang Sujana; I Gede Agus Pertama Yudantara (Jurnal Ilmiah Akuntansi dan Humanika, 2022)
This study aims to determine the application of the biological asset financial recording system based on SAK-EMKM in the laying hen’s business. This research was conducted at the " Ayodhya Farm " laying hens farm, Sukawana Village, Kintamani District, Bangli Regency, Bali. This study used qualitative research methods. The first data collection in this study was conducted through interviews with laying hens’ business owners and employees, the second was observation, and the last was documentation. The data analysis technique used in this research is data reduction, data display, and data verification. The results of this study are the first in terms of the recognition of biological assets and agricultural products produced, including having complied with the cues of making financial statements in accordance with PSAK 69 on Agriculture, the second in terms of measuring biological assets and agricultural products that have not been fully carried out, the third in terms of measurement of biological assets and agricultural products. In terms of presentation and disclosure, this business still uses simple reports. However, it is hoped that later it will be able to report in accordance with PSAK 69 and SAK-EMKM.